2021
DOI: 10.1177/00031348211023395
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Perioperative Peripheral Nerve Blocks on Peri- and Postoperative Opioid Use and Pain Management

Abstract: Introduction The amount of peri- and post-operative use of opioids for pain management, and the duration in which they are used following surgery, are positively associated with the likelihood of subsequent opioid use and addiction. Aware of this issue, many clinicians are seeking ways to reduce opioid use while maintaining adequate pain management. Recent evidence suggests that peripheral nerve block utilization may present a viable mechanism by which clinicians can accomplish this goal. Methods Ovid MEDLINE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…This study showed an association between reduced MME/kg usage and pain scores in the block group, indicating that nerve blocks are associated with reduced MMEs in selected patients. This finding is consistent with using peripheral nerve blocks in other surgeries [ 11 , 12 , 13 ]. Minimizing pain and discomfort can improve the child’s and parents’ overall experience and reduce anxiety.…”
Section: Discussionsupporting
confidence: 91%
“…This study showed an association between reduced MME/kg usage and pain scores in the block group, indicating that nerve blocks are associated with reduced MMEs in selected patients. This finding is consistent with using peripheral nerve blocks in other surgeries [ 11 , 12 , 13 ]. Minimizing pain and discomfort can improve the child’s and parents’ overall experience and reduce anxiety.…”
Section: Discussionsupporting
confidence: 91%
“…Peripheral nerve blocks (PNBs) have been effective in treatment of acute and chronic headache disorders that involve the trigeminalovascular system, such as migraines, neuralgias, tension-type and chronic headaches ( 12–14 ). PNBs reduce headache intensity, duration and opioid usage ( 14 , 15 ). Recently, a case report described success of a greater occipital nerve block for HASH in two patients ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Despite the widely accepted knowledge that PNB decrease pain scores as well as opioid consumption and associated side-effects, their utilization is not ubiquitous. 15 Significant translational science and quality improvement (QI) initiatives are still required to ensure that patients who are suitable candidates for PNB receive this analgesia modality. At our institution, approximately 75 AFSs are completed each year.…”
Section: Introductionmentioning
confidence: 99%